QS1: Regret After Gender Affirmation Surgery. (July 2021) - Bustos, Valeria P.; Bustos, Samyd S.; Escandón, Joseph M.; Mascaro, Andres; Del Corral, Gabriel; Gaxiola-García, Miguel Angel; Kushida-Contreras, Beatriz Hatsue; Langstein, Howard N.; Manrique, Oscar J.
Abstract : Purpose : There is an unknown percentage of transgender and gender non-confirming individuals who undergo gender affirmation surgeries (GAS) that experiences regret. Regret could lead to physical and mental morbidity, also questioning the appropriateness of these procedures in selected patients. The aim of this study is to evaluate the prevalence of regret in transgender individuals who underwent GAS and evaluate associated factors. Methods : A systematic review was conducted following the PRISMA guidelines. A comprehensive research strategy was performed including the following databases: Ovid MEDLINE(R) and Epub Ahead of Print, In-Process & Other Non-Indexed Citations, and Daily, Ovid EMBASE, Ovid Cochrane Central Register of Controlled Trials, Ovid Cochrane Database of Systematic Reviews, and Scopus. Random-effects meta-analysis of proportions, subgroup analysis, meta-regression, publication bias, and sensitivity analyses were performed. Results: A total of 27 studies, pooling 7, 928 transgender patients that underwent any type of GAS were included in this review. The pooled prevalence of regret after GAS was 1% (95% Confidence interval [CI] <1-2%). Overall, 33% underwent transmasculine surgical procedures and 67% transfeminine procedures. The prevalence of regrets among patients undergoing transmasculine and transfeminine surgeries was <1% (IC<1-<1%) and 1% (CI<1-2%), respectively. A total of 77 patients regretted having had GAS. Of them, 28 had minor and 34 had major regrets based on Pfäfflin's regret classification. The majority of these had "clear regret" based on Kuiper and Cohen Kettenis' classification. Conclusion: Based on this review, there is an extremely low prevalence of regret in transgender patients after GAS. We believe this study corroborates the improvements made in regard to selection criteria for GAS. However, there is high subjectivity in the assessment of regret and lack of standardized questionnaires, which highlight the importance of developing validated questionnaires in this population.